Fronteiras índias nos “dezertos, ainda indecizos, pella linha imaginária”. Século XVIII - Glória Kok (Centre de Recherches sur les Mondes Américains, 2011)
This article deals with the conflicts that happened in the extreme West of Portuguese America, at the beginning of the process of expropriation of the Indian´s lands by Paulistas during the 18th century.The discovery of the gold mines in Cuiabá (1718) and in Goiás (1725) increased the confrontations and the negotiations among groups of Indians in the region: the southern Kaiapó, who occupied from the southwestern of Mato Grosso until the mouth of the Araguaia River; the Mbayá-Guaycuru, who were spred throughout the central and southern of the Chaco; and the Payaguá, who were controlled the Paraguai and Cuiabá rivers.However, these indigenous groups who took advantage of the disputations between the Spanish and the Portuguese Crowns in the Iberians frontiers had articulated politic and commercial extremely versatile strategies. Consequently, they could establish several partnerships either with the Portuguese, the Spanish or the indigenous groups. In this colonial scenario, new indigenous identities developed and politically organized being capable of making the deals with Iberians authorities.On the other hand, the troops of the paulistas who had been formed to fight against the Indians were characterized by the ethnic diversity and they had developed efficient war conquest strategies in the South America frontiers.